Chronic kidney disease in TARS2-related mitochondrial disease - A case report - Aleksandra Paripović; Nataša Stajić; Jovana Putnik; Slavica Ostojić; Biljana Alimpić; Adrijan Sarajlija (Elsevier, 2024)
This case report describes a patient harboring TARS2 mutations where chronic kidney disease stands out as the predominant clinical feature. The distinct manifestation observed in this case underscores the importance of continual exploration and documentation of diverse clinical presentations associated with TARS2 mutations, contributing to an enriched comprehension of the spectrum of effects linked to this genetic variation